Food science and technology bulletin functional foods. Volume 5 - Gibson, Glenn R. (IFIS, 2009)
This book is a journal that delivers concise and relevant peer-reviewed minireviews of developments in selected areas of functional foods.
Keywords: Functional foods.; Food industry and trade.; elektronické knihy; electronic books